A hydrogenation catalyst intermediate, a hydrogenation catalyst and preparation and use thereof
Patent Information
- Application Number
- CN202510570098.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-30
- Publication Date
- 2026-10-30
AI Technical Summary
当前,普通氧化铝酸性较为单一、负载金属时与活性组分间的作用太强,导致深度加氢的目的还不能很好的实现
[0042]本发明提供了一种加氢催化剂中间体,所述催化剂中间体包括介孔氧化铝、活性炭和和第VIB族金属;所述催化剂中间体包括大孔和介孔,其中孔径为6.0~25.0nm的介孔孔容占总孔容的10.0%~38.0%,孔径为50.0~300.0nm的大孔孔容占总孔容的40.0%~55.0%。本发明加氢催化剂中间体同时具有介孔和大孔且二者分布适宜,两种孔道互相配合,共同发挥作用,使得中间体的孔道分布更加优异;优选地,所述加氢催化剂中间体具有适宜的B酸占比,更有利于提高催化剂的氢解性能。以本发明加氢催化剂中间体为基础制备得到的加氢催化剂,用于渣油加氢脱金属反应中,各组分相互配合,加氢活性大幅提高,能够保证加氢装置的长周期稳定运行。
Smart Images

Figure BDA0005386945910000101 
Figure BDA0005386945910000102 
Figure BDA0005386945910000111
Abstract
Description
Technical Field
[0001] This invention relates to a hydrogenation catalyst, specifically to a hydrogenation catalyst intermediate, the hydrogenation catalyst itself, and its preparation and application. Background Technology
[0002] With the increasing trend of heavier and lower-quality crude oil worldwide, heavy oil hydrotreating technology plays an increasingly important role in the efficient utilization and lightening of crude oil. Alumina, as the main carrier of hydrotreating catalysts, possesses characteristics such as a large specific surface area, excellent pore structure, a certain acid strength distribution, and high hydrothermal and thermal stability, playing a crucial role in the hydrotreating process. Currently, ordinary alumina has relatively simple acidity, and the interaction between loaded metals and active components is too strong, preventing the full realization of deep hydrotreating goals. Especially in the hydrotreating of heavy oil, the small pore size of ordinary alumina restricts the diffusion of large molecules during the reaction, making the catalyst more prone to deactivation, and the utilization rate of active metals needs further improvement.
[0003] CN103539173A discloses a method for preparing a highly thermally stable ordered mesoporous alumina material. This material maintains good pore order after calcination at 1000℃ for 1 hour. It uses inorganic aluminum sources such as aluminum nitrate and aluminum chloride as raw materials, P123 as a template agent, and organic carboxylic acids as surface protectants in ethanol and aqueous solutions. The ordered mesoporous alumina material is synthesized through solvent evaporation-induced self-assembly. The pore size of this material is 4.0–10.0 nm, and the specific surface area is 200–400 m². 2 / g, pore volume 0.3~1.0cm³ 3 g / .
[0004] Currently, there are many ways to synthesize alumina, but how to prepare an alumina-based support material with better overall performance, and on the basis of the above, prepare a hydrogenation catalyst with excellent hydrogenation demetallization performance, is an important research direction. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides a hydrogenation catalyst intermediate, a hydrogenation catalyst, and its preparation and application. The hydrogenation catalyst of this invention, used in the hydrodemetallization reaction of residual oil, exhibits strong hydrogenation activity, significantly improving its reaction performance and ensuring long-term stable operation of the hydrogenation unit.
[0006] The first aspect of the present invention provides a hydrogenation catalyst intermediate, wherein the hydrogenation catalyst intermediate comprises mesoporous alumina, activated carbon, and a Group VIB metal; the hydrogenation catalyst intermediate comprises macropores and mesopores, wherein the pore volume of mesopores with a pore size of 6.0–25.0 nm accounts for 10.0%–38.0% of the total pore volume, preferably 30.0%–34.0%, and the pore volume of macropores with a pore size of 50.0–300.0 nm accounts for 40.0%–55.0% of the total pore volume, preferably 42.0%–50.0%.
[0007] Further, in the hydrogenation catalyst intermediate, the amount of Brønsted acid accounts for 20.0% to 30.0% of the sum of the amounts of Brønsted acid and Lewis acid, preferably 26.0% to 30.0%. In the hydrogenation catalyst intermediate, the amount of Brønsted acid is 19.5 to 30.0 μmol / g, preferably 25.5 to 30.0 μmol / g.
[0008] Furthermore, the specific surface area of the mesoporous alumina is 300–500 m² / g. 2 / g, preferably 330-360m 2 / g, with a mesopore size of 11.0–25.0 nm, preferably 14.0–17.0 nm, and a pore volume of 0.95–1.50 mL / g, preferably 1.10–1.50 mL / g.
[0009] Furthermore, the mesoporous alumina contains at least 53% of the medium-strong acid content, preferably 58% to 65% of the total acid content. The total acid content refers to the sum of the weak acid content, the medium-strong acid content, and the strong acid content, and the unit of acid content is mmol / g. In the modified mesoporous alumina, the total acid content is 0.230 to 0.277 mmol / g, preferably 0.230 to 0.250 mmol / g.
[0010] Furthermore, in the hydrogenation catalyst intermediate, based on the mass of the hydrogenation catalyst intermediate, the content of Group VIB metals as oxides is 5% to 25%, preferably 5% to 15%.
[0011] Furthermore, in the hydrogenation catalyst intermediate, the mass ratio of mesoporous alumina to activated carbon is 1.0 to 6.0, preferably 2.0 to 5.0.
[0012] A second aspect of the present invention provides a method for preparing the above-mentioned hydrogenation catalyst intermediate, comprising the following steps:
[0013] (1) Mix aluminum source, acid and alcohol, and perform pre-hydrolysis to obtain solution A;
[0014] (2) Mix the template agent and alcohol to obtain solution B;
[0015] (3) Mix solution A, solution B and mixture X containing bifunctional structure directing agent and perform hydrothermal treatment, then dry and calcinate to obtain mesoporous alumina;
[0016] (4) The mesoporous alumina, activated carbon, group VIB metal source and molding aid obtained in step (3) are mixed and shaped, dried and calcined to obtain a hydrogenation catalyst intermediate.
[0017] Further, in step (1), the pre-hydrolysis is carried out under stirring conditions, and the stirring rate is not particularly limited. The temperature of the pre-hydrolysis is 20-60℃, and the pre-hydrolysis time is 1-12 hours. Further, the aluminum source is one or more of aluminum nitrate, aluminum chloride, and aluminum isopropoxide. The acid is an inorganic acid, preferably one or more of sulfuric acid, nitric acid, and hydrochloric acid. The alcohol is a low-carbon alcohol, preferably one or more of ethanol, propanol, and butanol.
[0018] Further, in step (1), the alcohol / aluminum molar ratio is 10.0 to 80.0, preferably 10.0 to 50.0.
[0019] Further, in step (1), the acid / aluminum molar ratio is 1.0 to 12.0, preferably 3.0 to 8.0.
[0020] Further, preferably, in step (1), the aluminum source, acid, and alcohol are first mixed and pre-hydrolyzed to obtain a precursor solution, and then an ionic emulsifier is added dropwise to the precursor solution to obtain solution A. The amount of the ionic emulsifier added is related to the amount of the precursor solution by 5–15 g / 100 mL.
[0021] Furthermore, the ionic emulsifier is one or more of anionic emulsifiers such as sodium dodecyl sulfate and fatty polyoxyethylene ether sulfate salt (chemical structure formula RO(CH2CH2O)n-SO3Na (n=1~15, R is a fatty alkyl group of C10~C22)).
[0022] Further, in step (2), the template agent is at least one of P123 (polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer), SDBS (sodium dodecylbenzenesulfonate) and AOT (dioctyl sulfosuccinic acid), preferably P123.
[0023] Further, the molar ratio of the aluminum source in step (1) to the template agent in step (2) is 50–120, preferably 60–80. Further, after mixing, the mixture is stirred at 25–60°C for 1–5 hours, with no particular limitation on the stirring rate. In step (2), the alcohol is one or more low-carbon organic alcohols such as ethanol, propanol, and butanol. The molar ratio of the alcohol to the template agent is 300–1000.
[0024] Further, in step (3), the mixture X containing the bifunctional structure directing agent includes the bifunctional structure directing agent, an alcohol and an acid, wherein the alcohol is preferably ethanol and the acid is preferably nitric acid; the bifunctional structure directing agent is polyethylene glycol-distearatephosphatidylethanolamine (molecular weight of 500-5000).
[0025] Further, in step (3), the volume ratio of alcohol to acid in the mixture X is 4 to 12. In the mixture X, the ratio of the mass of the bifunctional directed agent to the sum of the volumes of alcohol and acid is 0.05 to 0.65 g / mL, preferably 0.40 to 0.65 g / mL.
[0026] Furthermore, in step (3), the ratio of the molar amount of the bifunctional structure directing agent to the sum of the molar amounts of the bifunctional structure directing agent and the aluminum source in solution A is 0.1 to 0.5.
[0027] Preferably, in step (3), solution A is first added dropwise to solution B to obtain solution C; then, the mixture X containing the bifunctional structure directing agent is added dropwise to solution C for hydrothermal treatment. Further, the conditions for the hydrothermal treatment are: temperature 160-280℃, preferably 180-260℃, time 3-12h, preferably 4-8h.
[0028] Further, in step (3), after the hydrothermal treatment, the alumina is first cooled to 25°C, then dried and calcined to obtain mesoporous alumina. The drying temperature is 120–200°C, and the drying time is 4–10 hours. The calcination temperature is 500–650°C, and the calcination time is 3–8 hours.
[0029] Further, in step (4), the activated carbon is a high-temperature activated carbon, with a minimum heat resistance temperature of not less than 700℃, preferably 750~900℃. The activated carbon has a pore volume of 1.0~1.8mL / g, and the pore volume with a pore size of 50.0~300.0nm accounts for 15%~40% of the total pore volume.
[0030] Further, in step (4), the molding aid is one or more of guar gum powder, methylcellulose, etc. The molding method can be at least one of extrusion, tableting, and ball rolling. The shaped product can be clover-shaped, four-leaf clover-shaped, butterfly-shaped, cylindrical, spherical, or strip-shaped, etc.
[0031] Further, in step (4), the mass of the molding aid added is 1.0% to 8.0% of the total mass of mesoporous alumina and activated carbon.
[0032] Further, in step (4), the Group VIB metal is preferably molybdenum; further, the molybdenum source is selected from at least one of ammonium heptamolybdate, ammonium tetramolybdate, etc. The mass of the Group VIB metal source, calculated as oxide, is 10% to 18% of the total mass of mesoporous alumina and activated carbon.
[0033] Further, in step (4), the drying temperature is 120–200°C, and the drying time is 4–10 h. The calcination temperature is 500–650°C, and the calcination time is 3–8 h.
[0034] A third aspect of the present invention provides a hydrogenation catalyst comprising a hydrogenation catalyst intermediate and a Group VIII metal.
[0035] Furthermore, nickel is preferred among Group VIII metals.
[0036] Furthermore, in the hydrogenation catalyst, the content of Group VIII metal oxide is 0.5% to 10.0% based on the mass of the hydrogenation catalyst, preferably 0.5% to 6.0%.
[0037] Furthermore, the pore size of the hydrogenation catalyst is in the range of 16.0 to 20.0 nm, preferably 18.0 to 20.0 nm.
[0038] The fourth aspect of the present invention provides a method for preparing the above-mentioned hydrogenation catalyst, comprising: loading a Group VIII metal onto the above-mentioned catalyst intermediate, calcining, and obtaining the catalyst.
[0039] Furthermore, the preferred loading method is saturated impregnation. After impregnation, the catalyst is subjected to conventional filtration, washing, drying, and calcination to obtain the catalyst. The drying temperature is 120–200°C, and the drying time is 4–10 hours. The calcination temperature is 500–650°C, and the calcination time is 3–8 hours.
[0040] The fifth aspect of this invention provides the application of the above-mentioned hydrogenation catalyst in the hydrodemetallization of residue oil.
[0041] Compared with the prior art, the present invention has the following beneficial effects:
[0042] This invention provides a hydrogenation catalyst intermediate comprising mesoporous alumina, activated carbon, and a Group VIB metal. The intermediate includes macropores and mesopores, wherein mesopores with a pore size of 6.0–25.0 nm account for 10.0%–38.0% of the total pore volume, and macropores with a pore size of 50.0–300.0 nm account for 40.0%–55.0% of the total pore volume. This hydrogenation catalyst intermediate possesses both mesopores and macropores in a suitable distribution, with the two types of pores working in tandem to achieve a superior pore distribution. Preferably, the intermediate has a suitable proportion of Brønsted acid, which further enhances the hydrogenolysis performance of the catalyst. The hydrogenation catalyst prepared based on this intermediate, when used in the hydrodemetallization reaction of residual oil, exhibits excellent synergy among its components, significantly improving hydrogenation activity and ensuring long-term stable operation of the hydrogenation unit.
[0043] This invention provides a method for preparing a hydrogenation catalyst intermediate. First, a self-assembly method is used, mainly by controlling the alcohol / aluminum molar ratio, the alcohol / template molar ratio, and the introduction method of the template agent. At the same time, a bifunctional structure directing agent is introduced during the self-assembly process, combined with hydrothermal treatment, to prepare mesoporous alumina with more suitable specific surface area, pore structure, and surface acid distribution. Then, based on the above-mentioned mesoporous alumina material, it is mixed with high-temperature activated carbon with macropores and a main active metal (Group VIB metal) to prepare a hydrogenation catalyst intermediate with more suitable pore distribution and Brønsted acid ratio.
[0044] Based on the hydrogenation catalyst intermediate of this invention, a hydrogenation catalyst is prepared. Through comprehensive coordination of each step, the obtained hydrogenation catalyst is used in the hydrodemetallization reaction of residue oil, and the stability of the catalyst is significantly enhanced. Detailed Implementation
[0045] The technical solutions and effects of the present invention will be further illustrated below with reference to the embodiments, but the invention is not limited to the following embodiments.
[0046] In this invention, the specific surface area and pore volume of the samples were characterized using a Micromeritics ASAP2420 fully automated specific surface area analyzer from Micromeritics, Inc., USA. The treated samples were loaded into the fully automated specific surface area analyzer for property testing using a low-temperature nitrogen isothermal adsorption method. The specific surface area of the samples was calculated using the BET method.
[0047] In this invention, the determination of L-acid or Brønsted acid is performed using infrared spectroscopy. The instrument used is a Nicot Fourier Transform Infrared Spectrometer-6700 (USA). The determination method is as follows: The sample to be measured is ground and pressed into a thin sheet with a thickness of approximately 0.1 mm, which is then placed in an infrared cell. The in-situ infrared cell is heated from room temperature to 350 °C over a programmed temperature range of 20 min and held for 120 min, then cooled to 200 °C over a 10 min period. The in-situ cell is then evacuated to a vacuum of 0.01 Pa. The sample is scanned as the background spectrum, and pyridine vapor is used as a probe molecule to scan the sample at 200 °C. The total amount of total acid, Brønsted acid, and L-acid can then be obtained. The units for the amounts of Brønsted acid and L-acid are μmol / g.
[0048] In this invention, the acid content of moderately strong acids was determined using the NH3-TPD method. The instrument used was an Auto-ChemII 2920 chemisorption analyzer from Micron Instruments. Ammonia was used as the adsorption / desorption medium, and helium as the carrier gas. Programmed temperature desorption and chromatographic analysis were employed to obtain the acid content in different desorption temperature ranges. The acid content of weak acids corresponds to an ammonia desorption temperature below 200℃, the acid content of moderately strong acids corresponds to an ammonia desorption temperature of 200℃–400℃, and the acid content of strong acids corresponds to an ammonia desorption temperature above 400℃. The unit of acid content is mmol / g, which represents the amount of ammonia adsorbed per gram of molecular sieve. The sum of the acid content of weak, moderately strong, and strong acids is the total acid content.
[0049] In various embodiments of the present invention, the molecular weight of the bifunctional structure-directing agent polyethylene glycol-distearatephosphatidylethanolamine is 872.14.
[0050] Example 1
[0051] Preparation of the catalyst intermediate in this example:
[0052] (1) Add 102g of aluminum isopropoxide and 90mL of acid to 400mL of ethanol, stir at 25℃ for 4h to perform pre-hydrolysis and obtain a precursor solution; add 35g of sodium dodecyl sulfate to the precursor solution and continue stirring for 3h to obtain solution A.
[0053] (2) Add 45g of template agent P123 to 300mL of ethanol, stir at 25℃ for 6h to obtain solution B;
[0054] (3) Solution A was added dropwise to B to obtain solution C; 60g of bifunctional structure directing agent polyethylene glycol-distearatephosphatidylethanolamine was prepared with 100mL ethanol and 10mL nitric acid to form solution X. Solution X was added dropwise to solution C and stirred for 2h. Then, it was transferred to a hydrothermal reactor for hydrothermal treatment at 180℃ for 5h. After hydrothermal treatment, it was cooled to 25℃ to obtain solution D; solution D was placed in an oven at 180℃ and the solvent was automatically evaporated until the sample was dry. Then, it was calcined in a muffle furnace at 550℃ for 3h to obtain mesoporous alumina.
[0055] (4) 260g of mesoporous alumina, 140g of high-temperature activated carbon (heat resistance temperature of 800℃, pore volume of 1.4mL / g, and pore size of 50~300nm accounting for 25% of the total pore volume), 5.2g of guar gum powder, 76g of ammonium heptamolybdate and deionized water were extruded into strips, dried at 120℃ for 6h and calcined at 600℃ for 4h to obtain the catalyst intermediate.
[0056] Preparation of the catalyst in this example:
[0057] Take 37g of nickel nitrate and 552g of deionized water to prepare an impregnation solution containing metallic nickel. Then, saturate the catalyst intermediate obtained above with the solution. After drying at 120℃ for 4h and calcining at 550℃ for 3h, the catalyst is obtained.
[0058] Example 2
[0059] Preparation of the catalyst intermediate in this example:
[0060] (1) Add 41g of aluminum isopropoxide and 64mL of acid to 360mL of ethanol, stir at 25℃ for 4h to perform pre-hydrolysis and obtain a precursor solution; add 57g of sodium dodecyl sulfate to the precursor solution, continue stirring for 3h to obtain solution A.
[0061] (2) Add 18g of template agent P123 to 162mL of ethanol, stir at 25℃ for 6h to obtain solution B;
[0062] (3) Solution A was added dropwise to B to obtain solution C; 65g of bifunctional structure directing agent polyethylene glycol-distearatephosphatidylethanolamine was prepared with 90mL of ethanol and 18mL of nitric acid to form solution X. Solution X was added dropwise to solution C and stirred for 2h. Then, it was transferred to a hydrothermal reactor for hydrothermal treatment at 190℃ for 5h. After hydrothermal treatment, it was cooled to 25℃ to obtain solution D; solution D was placed in an oven at 180℃ and the solvent was automatically evaporated until the sample was dry. Then, it was calcined in a muffle furnace at 550℃ for 3h to obtain mesoporous alumina.
[0063] (4) 180g of mesoporous alumina, 80g of high-temperature activated carbon (heat resistance temperature of 800℃, pore volume of 1.4mL / g, and pore size of 50~300nm accounting for 25% of the total pore volume), 9.6g of guar gum powder, 52g of ammonium heptamolybdate and deionized water were extruded into strips, dried at 120℃ for 6h and calcined at 600℃ for 4h to obtain the catalyst intermediate.
[0064] Preparation of the catalyst in this example:
[0065] Take 26g of nickel nitrate and 343g of deionized water to prepare an impregnation solution containing metallic nickel. Then, saturate the catalyst intermediate obtained above with the solution. After drying at 120℃ for 4h and calcining at 550℃ for 3h, the catalyst is obtained.
[0066] Example 3
[0067] Preparation of the catalyst intermediate in this example:
[0068] (1) Add 38g of aluminum isopropoxide and 25mL of acid to 460mL of ethanol, stir at 25℃ for 4h to perform pre-hydrolysis and obtain a precursor solution; add 52g of sodium dodecyl sulfate to the precursor solution, continue stirring for 3h to obtain solution A.
[0069] (2) Add 14g of template agent P123 to 105mL of ethanol, stir at 25℃ for 6h to obtain solution B;
[0070] (3) Solution A was added dropwise to B to obtain solution C; 84g of bifunctional structure directing agent polyethylene glycol-distearatephosphatidylethanolamine was prepared with 150mL ethanol and 17mL nitric acid to form solution X. Solution X was added dropwise to solution C and stirred for 2h. Then, it was transferred to a hydrothermal reactor for hydrothermal treatment at 185℃ for 5h. After hydrothermal treatment, it was cooled to 25℃ to obtain solution D; solution D was placed in an oven at 180℃ and the solvent was automatically evaporated until the sample was dry. Then, it was calcined in a muffle furnace at 550℃ for 3h to obtain mesoporous alumina.
[0071] (4) 254g of mesoporous alumina, 67g of high-temperature activated carbon (heat resistance temperature of 750℃, pore volume of 1.2mL / g, and pore size of 50~300nm accounting for 20% of the total pore volume), 8g of guar gum powder, 62g of ammonium heptamolybdate and deionized water were extruded into strips, dried at 120℃ for 6h and calcined at 600℃ for 4h to obtain the catalyst intermediate.
[0072] Preparation of the catalyst in this example:
[0073] Take 31g of nickel nitrate and 424g of deionized water to prepare an impregnation solution containing metallic nickel. Then, saturate the catalyst intermediate obtained above with the solution. After drying at 120℃ for 4h and calcining at 550℃ for 3h, the catalyst is obtained.
[0074] Example 4
[0075] Preparation of the catalyst intermediate in this example:
[0076] (1) Add 62g of aluminum isopropoxide and 35mL of acid to 420mL of ethanol, stir at 25℃ for 4h to perform pre-hydrolysis and obtain a precursor solution; add 50g of sodium dodecyl sulfate to the precursor solution, continue stirring for 3h to obtain solution A.
[0077] (2) Add 20g of template agent P123 to 95mL of ethanol, stir at 25℃ for 6h to obtain solution B;
[0078] (3) Solution A was added dropwise to B to obtain solution C; 45g of bifunctional structure directing agent polyethylene glycol-distearatephosphatidylethanolamine was prepared with 260mL of ethanol and 25mL of nitric acid to form solution X. Solution X was added dropwise to solution C and stirred for 2h. Then, it was transferred to a hydrothermal reactor for hydrothermal treatment at 160℃ for 5h. After hydrothermal treatment, it was cooled to 25℃ to obtain solution D; solution D was placed in an oven at 180℃ and the solvent was automatically evaporated until the sample was dry. Then, it was calcined in a muffle furnace at 550℃ for 3h to obtain mesoporous alumina.
[0079] (4) 300g of mesoporous alumina, 58g of high-temperature activated carbon (heat resistance temperature of 800℃, pore volume of 1.3mL / g, and pore size of 50~300nm accounting for 27% of the total pore volume), 6g of guar gum powder, 69g of ammonium heptamolybdate and deionized water were extruded into strips, dried at 120℃ for 6h and calcined at 600℃ for 4h to obtain the catalyst intermediate.
[0080] Preparation of the catalyst in this example:
[0081] Take 35g of nickel nitrate and 473g of deionized water to prepare an impregnation solution containing metallic nickel. Then, saturate the catalyst intermediate obtained above with the solution. After drying at 120℃ for 4h and calcining at 550℃ for 3h, the catalyst is obtained.
[0082] Example 5
[0083] Preparation of the catalyst intermediate in this example:
[0084] (1) Add 38g of aluminum isopropoxide and 42mL of acid to 380mL of ethanol, stir at 25℃ for 4h to perform pre-hydrolysis and obtain a precursor solution; add 66g of sodium dodecyl sulfate to the precursor solution, continue stirring for 3h to obtain solution A.
[0085] (2) Add 21g of template agent P123 to 108mL of ethanol, stir at 25℃ for 6h to obtain solution B;
[0086] (3) Solution A was added dropwise to B to obtain solution C; 24g of bifunctional structure directing agent polyethylene glycol-distearatephosphatidylethanolamine was prepared with 220mL ethanol and 32mL nitric acid to form solution X. Solution X was added dropwise to solution C and stirred for 2h. Then, it was transferred to a hydrothermal reactor for hydrothermal treatment at 160℃ for 5h. After hydrothermal treatment, it was cooled to 25℃ to obtain solution D; solution D was placed in an oven at 180℃ and the solvent was automatically evaporated until the sample was dry. Then, it was calcined in a muffle furnace at 550℃ for 3h to obtain mesoporous alumina.
[0087] (4) 260g of mesoporous alumina, 45g of high-temperature activated carbon (heat resistance temperature of 850℃, pore volume of 1.5mL / g, and pore size of 50~300nm accounting for 18% of the total pore volume), 8g of guar gum powder, 60g of ammonium heptamolybdate and deionized water were extruded into strips, dried at 120℃ for 6h and calcined at 600℃ for 4h to obtain the catalyst intermediate.
[0088] Preparation of the catalyst in this example:
[0089] Take 31g of nickel nitrate and 403g of deionized water to prepare an impregnation solution containing metallic nickel. Then, saturate the catalyst intermediate obtained above with the solution. After drying at 120℃ for 4h and calcining at 550℃ for 3h, the catalyst is obtained.
[0090] Example 6
[0091] Preparation of the catalyst intermediate in this example:
[0092] (1) Add 102g aluminum isopropoxide and 90mL acid to 400mL ethanol, stir at 25℃ for 4h to perform pre-hydrolysis and obtain solution A;
[0093] (2) Add 45g of template agent P123 to 300mL of ethanol, stir at 25℃ for 6h to obtain solution B;
[0094] (3) Solution A was added dropwise to B to obtain solution C; 60g of bifunctional structure directing agent polyethylene glycol-distearatephosphatidylethanolamine was taken and mixed with 100mL ethanol and 10mL nitric acid to prepare solution X. Solution X was added dropwise to solution C and stirred for 2h. Then, it was transferred to a hydrothermal reactor for hydrothermal treatment at a temperature of 160℃ for 5h. After hydrothermal treatment, it was cooled to 25℃ to obtain solution D; solution D was placed in an oven at 180℃ and the solvent was automatically evaporated until the sample was dry. Then, it was calcined in a muffle furnace at 550℃ for 3h to obtain mesoporous alumina.
[0095] (4) 260g of mesoporous alumina, 140g of high-temperature activated carbon (heat resistance temperature of 800℃, pore volume of 1.4mL / g, and pore size of 50~300nm accounting for 25% of the total pore volume), 5.2g of guar gum powder, 76g of ammonium heptamolybdate and deionized water were extruded into strips, dried at 120℃ for 6h and calcined at 600℃ for 4h to obtain the catalyst intermediate.
[0096] The catalyst in this example was prepared according to the method described in Example 1.
[0097] Comparative Example 1
[0098] In this example, the mesoporous alumina was prepared according to the method in the literature ("P123 Preparation and properties of template alumina mesoporous materials." Journal of Dalian Railway Institute 27.1 (2006): 71-75), and the rest was the same as in Example 1.
[0099] Weigh 102g of aluminum isopropoxide and dissolve it in 400mL of deionized water. Add 90mL of nitric acid to form a sol. Stir the solution in an 80℃ water bath for 1 hour. When the solution cools to 25℃, weigh 45g of P123 and dissolve it in the solution. Stir for 1 hour. Then, transfer the solution to a stainless steel autoclave lined with polytetrafluoroethylene for hydrothermal reaction. The filling degree is 70%, the hydrothermal reaction temperature is 100℃, and the reaction time is 24 hours. After the hydrothermal reaction is completed, let the autoclave cool to 25℃ and dry the reaction product in an oven at 60℃. Then, calcine it in a muffle furnace at 550℃ for 3 hours to obtain mesoporous alumina.
[0100] The catalyst in this example was prepared according to the method in Example 1.
[0101] Comparative Example 2
[0102] In this example, steps (1), (2), and (3) of the catalyst intermediate preparation process are the same as in Example 1, except that high-temperature activated carbon is not added in step (4).
[0103] (4) 400g of mesoporous alumina, 5.2g of guar gum powder, 76g of ammonium heptamolybdate and deionized water were extruded into strips, dried at 120℃ for 6h and calcined at 600℃ for 4h to obtain the catalyst intermediate.
[0104] The catalyst in this example was prepared according to the method in Example 1.
[0105] Comparative Example 3
[0106] In this example, steps (1), (2), and (3) in the preparation of the catalyst intermediate are the same as in Example 1. The difference is that in step (4), the active metal molybdenum is not introduced, and the mass of MoO3 introduced into the catalyst by impregnation and loading with molybdenum-nickel impregnation solution is 100% of the total MoO3 loading in the catalyst.
[0107] Catalyst preparation in this example:
[0108] A nickel-molybdenum impregnation solution was prepared by mixing nickel nitrate, ammonium heptamolybdate, and deionized water. The solution was then used to saturate the catalyst intermediate obtained above. After drying at 120°C for 6 hours and calcining at 600°C for 4 hours, the catalyst was obtained.
[0109] The catalyst obtained in Comparative Example 3 has a pore size of 15.3 nm.
[0110] Comparative Example 4
[0111] In this example, the mesoporous alumina was prepared using the following method during the preparation of the catalyst intermediate, and the rest was the same as in Example 1.
[0112] (1) Add 102g of aluminum isopropoxide and 90mL of acid to 265mL of ethanol, stir at 25℃ for 4h to perform pre-hydrolysis and obtain a precursor solution; add 35g of sodium dodecyl sulfate to the precursor solution and continue stirring for 3h to obtain solution A.
[0113] (2) Add 45g of template agent P123 to 300mL of ethanol, stir at 25℃ for 6h to obtain solution B;
[0114] (3) Solution A was added dropwise to B to obtain solution C; 60g of bifunctional structure directing agent polyethylene glycol-distearatephosphatidylethanolamine was taken and mixed with 100mL ethanol and 10mL nitric acid to prepare solution X. Solution X was added dropwise to solution C and stirred for 2h. Then, it was transferred to a hydrothermal reactor for hydrothermal treatment at 180℃ for 5h. After hydrothermal treatment, it was cooled to 25℃ to obtain solution D; solution D was placed in an oven at 180℃ and the solvent was automatically evaporated until the sample was dry. Then, it was calcined in a muffle furnace at 550℃ for 3h to obtain mesoporous alumina.
[0115] The catalyst in this example was prepared according to the method in Example 1.
[0116] Comparative Example 5
[0117] In this example, the mesoporous alumina was prepared using the following method during the preparation of the catalyst intermediate, and the rest was the same as in Example 1.
[0118] (1) Add 102g of aluminum isopropoxide and 90mL of acid to 400mL of ethanol, stir at 25℃ for 4h to perform pre-hydrolysis and obtain a precursor solution; add 35g of sodium dodecyl sulfate to the precursor solution and continue stirring for 3h to obtain solution A.
[0119] (2) Add 45g of template agent P123 to 500mL of ethanol, stir at 25℃ for 6h to obtain solution B;
[0120] (3) Solution A was added dropwise to B to obtain solution C; 60g of bifunctional structure directing agent polyethylene glycol-distearatephosphatidylethanolamine was prepared with 100mL ethanol and 10mL nitric acid to form solution X. Solution X was added dropwise to solution C and stirred for 2h. The solution was then transferred to a hydrothermal reactor for hydrothermal treatment at 180℃ for 5h. After hydrothermal treatment, the solution was cooled to 25℃ to obtain solution D. Solution D was placed in an oven at 180℃ and the solvent was allowed to evaporate automatically until the sample was dry. The sample was then calcined in a muffle furnace at 550℃ for 3h to obtain mesoporous alumina.
[0121] The catalyst in this example was prepared according to the method in Example 1.
[0122] Table 1. Properties of the mesoporous alumina obtained in each example.
[0123]
[0124] Table 2. Composition and properties of the hydrogenation catalyst intermediates obtained in each example.
[0125]
[0126]
[0127] Note: *The percentage (%) of the amount of Brønsted acid to the sum of the amounts of Brønsted acid and L-acid in the obtained catalyst intermediate is represented by A;
[0128] **In the obtained catalyst intermediate, the proportion (%) of mesopores with a pore size of 6.0–25.0 nm to the total pore volume is represented by B; the proportion (%) of macropores with a pore size of 50.0–300.0 nm to the total pore volume is represented by C.
[0129] Table 3. Composition and properties of the hydrogenation catalysts obtained in each example.
[0130] Group VIII metal oxides, % Pore diameter, nm Example 1 1.99 19.5 Example 2 2.13 18.2 Example 3 2.07 18.6 Example 4 2.09 17.4 Example 5 2.17 16.5 Example 6 2.16 16.7 Comparative Example 1 2.03 15.6 Comparative Example 2 2.00 15.9
[0131] Evaluation test
[0132] Activity stability tests were conducted on Examples 1-6 and Comparative Examples 1-5 using a 200mL fixed-bed hydrogenation test apparatus. The feedstock was residue oil with a density of 980.5 kg / m³. 3 (20℃), S content 2.56wt%, Ni and V contents 25.7μg / g and 57.3μg / g respectively, CCR content 11.8wt%, the demetallization rate after 2000h of operation in Example 1 was 100%, and all others are relative demetallization rates. Specific experimental conditions are shown in Table 4, and experimental results are shown in Tables 5 and 6.
[0133] Table 4 Test Conditions
[0134] Reaction temperature, °C 380 Reaction pressure, MPa 15.7 <![CDATA[Liquid hourly volume space velocity, h -1 > 1.2 Hydrogen-to-oil ratio, V / V 750
[0135] Table 5. Test results of the hydrogenation demetallization catalysts in each example.
[0136]
[0137] Table 6. Experimental results of hydrogenation demetallization catalysts in each comparative example.
[0138]
[0139] The specific embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combining the various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A hydrogenation catalyst intermediate, characterized in that, The hydrogenation catalyst intermediate comprises mesoporous alumina, activated carbon, and a Group VIB metal; the hydrogenation catalyst intermediate comprises macropores and mesopores, wherein the mesopore volume with a pore size of 6.0–25.0 nm accounts for 10.0%–38.0% of the total pore volume, preferably 30.0%–34.0%, and the macropore volume with a pore size of 50.0–300.0 nm accounts for 40.0%–55.0% of the total pore volume, preferably 42.0%–45.0%.
2. The hydrogenation catalyst intermediate according to claim 1, characterized in that, In the hydrogenation catalyst intermediate, the amount of Brønsted acid accounts for 20.0% to 30.0% of the sum of the amounts of Brønsted acid and Lewis acid, preferably 26.0% to 30.0%.
3. The hydrogenation catalyst intermediate according to claim 1, characterized in that, The specific surface area of the mesoporous alumina is 300–500 m². 2 / g, preferably 330-360m 2 / g, with a mesopore size of 11.0–25.0 nm, preferably 14.0–17.0 nm, and a pore volume of 0.95–1.50 mL / g, preferably 1.10–1.50 mL / g.
4. The hydrogenation catalyst intermediate according to claim 1, characterized in that, The mesoporous alumina contains at least 53% medium-strong acid, preferably 58% to 65% of the total acid content.
5. The hydrogenation catalyst intermediate according to claim 1, characterized in that, In the hydrogenation catalyst intermediate, based on the mass of the hydrogenation catalyst intermediate, the content of Group VIB metals as oxides is 5% to 25%, preferably 5% to 15%. And / or, in the hydrogenation catalyst intermediate, the mass ratio of mesoporous alumina to activated carbon is 1.0 to 6.0, preferably 2.0 to 5.
0.
6. A method for preparing the hydrogenation catalyst intermediate according to any one of claims 1-5, comprising the following steps: (1) Mix aluminum source, acid and alcohol, and perform pre-hydrolysis to obtain solution A; (2) Mix the template agent and alcohol to obtain solution B; (3) Mix solution A, solution B and mixture X containing bifunctional structure directing agent and perform hydrothermal treatment, then dry and calcinate to obtain mesoporous alumina; (4) The mesoporous alumina, activated carbon, group VIB metal source and molding aid obtained in step (3) are mixed and shaped, dried and calcined to obtain a hydrogenation catalyst intermediate.
7. The preparation method according to claim 6, characterized in that, In step (1), the aluminum source is one or more of aluminum nitrate, aluminum chloride, and aluminum isopropoxide; the acid is an inorganic acid, preferably one or more of sulfuric acid, nitric acid, and hydrochloric acid; and the alcohol is a low-carbon alcohol, preferably one or more of ethanol, propanol, and butanol. And / or, in step (1), the temperature of the pre-hydrolysis is 20-60°C and the time of the pre-hydrolysis is 1-12h; And / or, in step (1), the ethanol / aluminum molar ratio is 10.0 to 80.0, preferably 10.0 to 50.0; And / or, in step (1), the acid / aluminum molar ratio is 1.0 to 12.0, preferably 3.0 to 8.
0.
8. The preparation method according to claim 6, characterized in that, In step (1), the aluminum source, acid and alcohol are first mixed and pre-hydrolyzed to obtain a precursor solution. Then, an ionic emulsifier is added dropwise to the precursor solution to obtain solution A. And / or, the ionic emulsifier is one or more of sodium dodecyl sulfate and fatty polyoxyethylene ether sulfate salt; Preferably, the amount of ionic emulsifier added is related to the amount of precursor solution used in a ratio of 5 to 15 g / 100 mL.
9. The preparation method according to claim 6, characterized in that, In step (2), the template agent is at least one of P123, SDBS and AOT, preferably P123; And / or, the molar ratio of aluminum source in step (1) to template agent in step (2) is 50 to 120, preferably 60 to 80; And / or, in step (2), the molar ratio of alcohol to template agent is 300 to 1000.
10. The preparation method according to claim 6, characterized in that, In step (3), the mixture X comprises a bifunctional structure directing agent, an alcohol, and an acid, wherein the bifunctional structure directing agent is polyethylene glycol-distearatephosphatidylethanolamine, the alcohol is preferably ethanol, and the acid is preferably nitric acid; And / or, in the mixture X, the mass ratio of the bifunctional directed agent to the sum of the volumes of the alcohol and acid is 0.05–0.65 g / mL, preferably 0.40–0.65 g / mL: And / or, in the mixture X, the volume ratio of alcohol to acid is 4 to 12; And / or, the ratio of the molar amount of the bifunctional structure directing agent to the sum of the molar amounts of the bifunctional structure directing agent and the aluminum source in solution A is 0.1 to 0.5; And / or, in step (3), the conditions for the hydrothermal treatment are: temperature 160-280℃, preferably 180-260℃, time 3-12h, preferably 4-8h; And / or, in step (3), the calcination temperature is 500-650°C and the calcination time is 3-8h.
11. The preparation method according to claim 6, characterized in that, In step (4), the activated carbon is a high-temperature activated carbon with a minimum heat resistance temperature of not less than 700°C, preferably 750-900°C; And / or, the activated carbon has a pore volume of 1.0 to 1.8 mL / g, and the pore volume of pores with a diameter of 50.0 to 300.0 nm accounts for 15% to 40% of the total pore volume.
12. The preparation method according to claim 6, characterized in that, In step (4), the molding aid is one or more of guar gum powder and methylcellulose; Preferably, the molding aid is added at a mass ratio of 1.0% to 8.0% of the total mass of mesoporous alumina and activated carbon.
13. The preparation method according to claim 6, characterized in that, In step (4), the Group VIB metal is molybdenum; Preferably, the mass of the Group VIB metal source, calculated as oxide, is 10% to 18% of the total mass of mesoporous alumina and activated carbon.
14. The preparation method according to claim 6, characterized in that, In step (4), the drying temperature is 120-200℃ and the drying time is 4-10h; And / or, the calcination temperature is 500–650°C, and the calcination time is 3–8 hours.
15. A hydrogenation catalyst comprising the hydrogenation catalyst intermediate of any one of claims 1-5 and a Group VIII metal.
16. The hydrogenation catalyst according to claim 15, characterized in that, The Group VIII metal is nickel; preferably, the content of Group VIII metal oxide in the hydrogenation catalyst is 0.5% to 10.0% based on the mass of the hydrogenation catalyst, more preferably 0.5% to 6.0%.
17. The hydrogenation catalyst according to claim 15, characterized in that, The hydrogenation catalyst has a pore size of 16.0–20.0 nm, preferably 18.0–20.0 nm.
18. The application of the hydrogenation catalyst according to claim 15, 16 or 17 in the hydrodemetallization of residue oil.
Citation Information
Patent Citations
Highly thermostable and ordered mesoporous alumina material and preparation method thereof
CN103539173A
